Femtosecond laser annealing effects on indium oxide nanowire transistors - Seongmin Kim; Sunkook Kim; Chunghun Lee; Srisungsitthisunti, P.; Pochiang Chen; Chongwu Zhou; Xianfan Xu; Minghao Qi; Mohammadi, S.; Sanghyun Ju; Janes, D.B. (2009 International Semiconductor Device Research Symposium, 2009)
We report the effects of annealing of the metal contacts to the nanowires using femtosecond laser pulses focused on the contact regions. The annealing induces significant shifts in the threshold voltage, and significantly reduces the drain conductance (gdS) of the nanowire transistors in the saturation region, along with modest improvements in the subthreshold slopes. Low frequency (1/f) noise measurements in these devices reveal that Hooge's constant is reduced following laser annealing presumably due to improved channel-metal interface and lowered Schottky barrier height.